RANCANG BANGUN BAK PEMBERSIH PART SEPEDA MOTOR UNTUK MENINGKATKAN EFISIENSI DAN KENYAMANAN KERJA MEKANIK - Rian Hardiansyah; Martoni (Universitas Widyatama, 2025)
Motorcycle maintenance and service activities require an effective and safe component cleaning process, both for the operator and the environment. The use of gasoline as a cleaning fluid has many disadvantages, including not being environmentally friendly, flammable, and potentially damaging rubber components. This research designs and builds a tool in the form of a motorcycle part cleaning tub with a closed circulation and filtration system, which uses engine degreaser liquid as an alternative cleaning fluid. The design process includes analyzing technical requirements, selecting materials such as stainless steel for the frame, and applying TIG (Tungsten Inert Gas) welding techniques to ensure the strength and durability of the tool. The filtration system allows the liquid to be used repeatedly, thus increasing efficiency and reducing hazardous material waste. Test results show that this tool is able to improve mechanic work comfort, keep the work area clean, and provide more optimal cleaning results. With its ergonomic and environmentally friendly system, it contributes to increased workshop productivity and supports sustainable work practices. This study shows that simple innovations in technical aids can have a significant impact on operational efficiency and safety aspects. Keywords: Cleaning tub, engine degreaser, filtration system.